An unforgettable trip to Tibet (September 12, 2024 - September 22, 2024) / Hoe Foo Terng - Hoe, Foo Terng (Academy of Language Studies, 2025)
As I am approaching retirement age. I want to use up my seven days of religious leave. It has been a longstanding wish to go to Tibet to worship Buddha. I started preparing in March - looking at various itineraries, enquiring from travel agencies, applying for religious leave and securing permission from the chancellery for an overseas trip. The application for the religious leave was a hassle because the university’s computerised leave application system was not designed to accommodate the application of religious leave by non- Muslims. After many attempts, the application had to be done manually i.e. filling out the printed form and submitting it by post.